Enhanced predictive signalling in schizophrenia. Issue 4 (18th January 2017) - Schmack, Katharina; Rothkirch, Marcus; Priller, Josef; Sterzer, Philipp
Abstract: Positive symptoms of schizophrenia such as delusions and hallucinations are thought to arise from an alteration in predictive mechanisms of the brain. Here, we empirically tested the hypothesis that schizophrenia is associated with an enhanced signalling of higher‐level predictions that shape perception into conformity with acquired beliefs. Twenty‐one patients with schizophrenia and twenty‐eight healthy controls matched for age and gender took part in a functional magnetic resonance imaging (fMRI) experiment that assessed the effect of an experimental manipulation of cognitive beliefs on the perception of an ambiguous visual motion stimulus. At the behavioural level, there was a generally weaker effect of experimentally induced beliefs on perception in schizophrenia patients compared with controls, but a positive correlation between the effect of beliefs on perception and the severity of positive symptoms. At the neural level, belief‐related connectivity between a region encoding beliefs in the orbitofrontal cortex (OFC) and a region encoding visual motion in the visual cortex (V5) was higher in patients compared with controls, indicating a stronger impact of cognitive beliefs on visual processing in schizophrenia. We suggest that schizophrenia might be associated with a generally weaker acquisition of externally generated beliefs and a compensatory increase in the effect of beliefs on sensory processing. Our current results are in line with the notion that enhanced signalling of higher‐level predictions that shape perception into conformity with acquired beliefs might underlie positive symptoms in schizophrenia. Hum Brain Mapp 38:1767–1779, 2017 . ©2017 Wiley Periodicals, Inc.